Influence of radiopaque fillers on physicochemical properties of a model epoxy resin-based root canal sealer - Fabricio Mezzomo COLLARES; Mariana KLEIN; Paula Dapper SANTOS; Fernando Freitas PORTELLA; Fabricio OGLIARI; Vicente Castelo Branco LEITUNE; Susana Maria Werner SAMUEL (University of São Paulo, 2013)
Objective: To verify the influence of radiopaque fillers on an epoxy resin-based sealer. Material and Methods: Experimental sealers were formulated by adding 20%, 40%, 60%, 80%, 100% and 120% of calcium tungstate, ytterbium trifluoride or barium sulphate by weight to an epoxy-resin-base. Setting time, flow, film thickness, radiopacity, sorption, solubility, pH and push-out bond strength were evaluated. Results: The setting time ranged from 373 to 612.66 min, the flow varied from 13.81±0.49 to 22.49±0.37 mm, and the film thickness ranged from 16.67±5.77 to 33.33±11.54 µm. The lowest pH was 5.47±0.53, and the highest was 6.99±0.03. Radiopacity varied from 0.38±0.04 to 2.57±0.21 mmAl and increased with the amount of filler. Calcium tungstate sealers had a higher sorption and solubility than other sealers. There was no significant difference in the push-out bond strength among the fillers at the 120% concentration. CONCLUSION: The inorganic fillers evaluated and their concentrations affect the physicochemical properties of an epoxy resin-based root canal sealer.